2014
DOI: 10.1097/aog.0000000000000141
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mode of Delivery With Urinary Incontinence and Changes in Urinary Incontinence Over the First Year Postpartum

Abstract: Vaginal delivery was associated with higher UI prevalence that persisted for 1 year postpartum, but there was no association with interference in daily life after 6 weeks postpartum. Variation was observed in UI changes within the first year in the vaginal delivery and cesarean delivery groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
2
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 39 publications
2
20
2
3
Order By: Relevance
“…These data are at odds with the present findings, where PFD was not prevalent in the immediate postpartum period, and although there was a clear trend toward a greater impact of urinary incontinence on QoL in the vaginal delivery group, the effect was not significant. In addition, the impact of urinary incontinence on QoL worsened during the 3 months of the study, in contrast to the findings by Chang et al., who reported a lower prevalence of urinary incontinence at 3 months postpartum than in the immediate postpartum period among women who underwent cesarean delivery.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…These data are at odds with the present findings, where PFD was not prevalent in the immediate postpartum period, and although there was a clear trend toward a greater impact of urinary incontinence on QoL in the vaginal delivery group, the effect was not significant. In addition, the impact of urinary incontinence on QoL worsened during the 3 months of the study, in contrast to the findings by Chang et al., who reported a lower prevalence of urinary incontinence at 3 months postpartum than in the immediate postpartum period among women who underwent cesarean delivery.…”
Section: Discussioncontrasting
confidence: 93%
“…Chang et al . found that the prevalence of urinary incontinence in the immediate postpartum period was higher among women who had a vaginal delivery, and the effect of urinary incontinence on QoL was more pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…Em relação ao tipo de parto, Oliveira et al (2013) (OR 2.59; p<0.001), Torrisi et al (2012) (OR 3,3;IC 95% 2,0-5,3;p<0,001), Ekström et al (2008) (RR 8,9;IC 95% 1,9-42 para IUE e RR 7,3; IC 95% 1,7-32 para IUU) e Chang et al (2014) …”
Section: Incontinência Urinária Após O Partounclassified
“…A influência do tipo de parto sobre a IU tem sido bastante estudada e geralmente é aceito que o parto vaginal ou instrumental e paridade estão associados a esta disfunção (Valeton, Amaral, 2011;Torrisi et al, 2012;Cerruto et al, 2013;Oliveira et al, 2013;Chang et al, 2014).…”
Section: Introductionunclassified
“…Results suggest that about half of women may develop genito-pelvic pain during pregnancy, which will persist for about a third, and a subset will develop this pain after childbirth [31].…”
Section: Biomedical Psychological and Relationship Factorsmentioning
confidence: 99%